[PP.23.02] LOW 25-HYDROXY-VITAMIN D PLASMA LEVELS ARE ASSOCIATED WITH A MORE SEVERE FORM OF PREECLAMPSIA: A CROSS-SECTIONAL STUDY. (September 2017) - Colussi, G.; Catena, C.; Driul, L.; Rossi, A.; Fagotto, V.; Pezzutto, F.; Martorana, L.; Sechi, L.A.
Abstract : Objective: Low levels of vitamin D have been associated with the occurrence of preeclampsia (PE) in pregnant women and, in some studies, vitamin D supplementation during pregnancy reduced the risk of PE and improved the glycometabolic profile. However, the relationship of plasma vitamin D levels with insulin-sensitivity and severity of PE has never been reported. The aim of this study was to examine the relationship between the gestational week of delivery as a marker of PE severity, the glycometabolic profile, and plasma 25-hydroxy-vitamin D (25OHVD) levels. Design and method: Sixty-nine consecutive multiethnic women with PE (35¡À6 y, 17% Africans, 80% Europeans, and 3% Hispanics) were enrolled in the study. General clinical characteristics, ambulatory blood pressure monitoring, plasma 25OHVD and parathormone (PTH) levels, glycometabolic profile, calcium metabolism, and renal function were evaluated in all women three weeks after delivery. Early onset PE was defined as delivery occurring before the 34th gestational week. Results: No women had taken 25OHVD supplementation before and during pregnancy. Prevalence of 25OHVD deficiency (<22 ng/ml) was 45%, insufficiency (<30 ng/ml) 23%, and normal levels 32%. Prevalence of early onset PE was higher in women with low 25OHVD levels than in those with normal levels (89% vs 11%; P = 0.007). Normal 25OHVD levels were observed in 40% of European women, whereas all African and Hispanic women had values below normal. 25OHVD levels were directly related with the gestational week of delivery (figure), plasma magnesium, and 24-h urinary calcium excretion, whereas its levels were inversely related with abortion number, 24-h urinary protein excretion, plasma glucose, insulin, and PTH levels, and homeostatic model assessment (HOMA) index. The relationship between HOMA index and gestational week of delivery was lost when 25OHVD was introduced in a multivariate model, but 25OHVD remained associated with gestational week of delivery independently of confounders. Conclusions: Low plasma levels of 25OHVD are independently associated with more severe PE suggesting potential benefits of 25OHVD supplementation in pregnant women at risk of PE. Figure. No caption available.